2011
DOI: 10.1007/s00122-010-1518-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of DArT markers in the Festuca–Lolium complex and their use in freezing tolerance association analysis

Abstract: Species belonging to the Festuca-Lolium complex are important forage and turf species and as such, have been studied intensively. However, their out-crossing nature and limited availability of molecular markers make genetic studies difficult. Here, we report on saturation of F. pratensis and L. multiflorum genetic maps using Diversity Array Technology (DArT) markers and the DArTFest array.The 530 and 149 DArT markers were placed on genetic maps of L. multiflorum and F. pratensis, respectively, with overlap of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 40 publications
5
34
0
Order By: Relevance
“…Investigations of introgressed material using in situ hybridisation have identified very small fescue segments in the genomes of the hybrid derivatives (Lideykytė et al 2006). Bartoš et al (2011) showed that )Festulolium Lp Fp -D-N (FuRs0357) contains genotypes with a high frost tolerance and were able to map and associate DArT markers to quantitative trait loci (QTLs) for frost tolerance. However, few fescue chromosomal segments were present in the frost tolerant genotypes and both diploid and tetraploid plants were found.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of introgressed material using in situ hybridisation have identified very small fescue segments in the genomes of the hybrid derivatives (Lideykytė et al 2006). Bartoš et al (2011) showed that )Festulolium Lp Fp -D-N (FuRs0357) contains genotypes with a high frost tolerance and were able to map and associate DArT markers to quantitative trait loci (QTLs) for frost tolerance. However, few fescue chromosomal segments were present in the frost tolerant genotypes and both diploid and tetraploid plants were found.…”
Section: Discussionmentioning
confidence: 99%
“…Changes from polycross to commercial seed generation were especially surveyed at those markers. In respect with mapping, Bartoš et al (2011) mapped 530 DArT markers in L. multiflorum. The present assay of 2,149 markers included 262 of those mapped markers, of which 29 belonged to the 151 Lm-specific markers previously identified.…”
Section: Methodsmentioning
confidence: 99%
“…DArT technology based on DNA restriction and hybridisation on a micro-array revealed to fulfil these requirements of robust system for broad genome coverage (Jaccoud et al 2001). It was first applied within the Festuca/Lolium complex of species by Kopecký et al (2009) with successful application to genotyping of Festulolium hybrids (Kopecký et al 2011) and to mapping in L. multiflorum and F. pratensis (Bartoš et al 2011).…”
mentioning
confidence: 99%
“…However, its efficient application requires markers linked to traits of interest. Bartoš et al (2011) were able to identify 96 DArT markers with significantly different distribution between high freezing tolerant and low freezing tolerant plants, but only five of these markers could be mapped on the F. pratensis genetic map. Colinearity with sequenced Brachypodium genome indicated the localization of a freezing tolerance QTL in the central part of chromosome 4 and a distal part of the short arm of chromosome 2 in Lolium and Festuca.…”
Section: Association Mapping and Marker Assisted Selectionmentioning
confidence: 95%